ROTASI “RODA KESEHATAN LANSIA” SEBAGAI STRATEGI LATIHAN FISIK UNTUK MENGURANGI RISIKO JATUH PADA LANSIA - Putri, Linta Meyla; Kristiani, Rina Budi; Mamesah, Marline Merke (Community Development in Health Journal, 2025)
Introduction & Aim: Elderly individuals experience various physical changes, including balance disorders and declining vision function, which increase the risk of falls. Falls among the elderly have become a major health concern that can significantly reduce their quality of life. Therefore, appropriate interventions, such as physical exercise, are necessary to help reduce the risk of falls. This program aims to improve balance and reduce fall risks among the elderly through a structured exercise program using the "Elderly Health Wheel" or ROTASI game. Method of Activity: The methods used include education and demonstrations of ROTASI-based physical exercises. Fall risk was measured using the Hendrich Fall Scale. Evaluations were conducted through pre-tests and post-tests to assess the cognitive level of the elderly after receiving the intervention. Results: A total of 21 elderly individuals participated in this activity. Evaluation results showed that before the intervention, 47.6% of the elderly had a moderate risk of falling. After participating in the program, there was an increase in the elderly's understanding and skills in maintaining balance, with 57.1% showing an improvement in post-test scores. Discussion: This program successfully increased elderly individuals' awareness of physical exercise and reduced their risk of falling. Additionally, elderly participants actively engaged in the ROTASI game showed improvements in body coordination, muscle strength, and flexibility. This activity also contributed to increased self-confidence and social participation among the elderly. Further implementation in various elderly communities is recommended to enhance their quality of life.